PENGARUH BERBAGAI JENIS KAPUR DALAM APLIKASI PENGAPURAN UNTUK MEMPERBAIKI SIFAT KIMIA ULTISOL - Amsar Maulana; H Herviyanti; Teguh Budi Prasetyo (Jurnal Tanah dan Sumberdaya Lahan, 2020)
Liming increases soil fertility through improved soil conditions in acidic soils (Ultisols). This study aimed to determine the effect of limes [CaO; Ca(OH)2; CaCO3 and CaMg(CO3)2 ] on the chemical properties of Ultisols of Limau Manis Padang. Treatments tested in this study application of four types of lime, i.e. A = CaO; B = Ca(OH)2; C = CaCO3; dan D = CaMg(CO3)2. on an Ultisol. A control treatment with no application of lime was also included in this study. After incubation of the soil-lime mixtures for two weeks, the results of the study showed that liming using dolomite [CaMg(CO3)2] was more effective in improving the chemical properties of Ultisols, compared to other types of lime [CaO; Ca(OH)2; CaCO3]. The effect of dolomite on 1*exchangeable Al (1 me Ca 100 g-1) improved chemical properties of an Ultisol from Limau Manis Padang such as pH H2O by 0.35 unit, available P by 1.03 ppm, exchangeable Al by 0.91 cmolc kg-1; exchangeable H by 0.92 cmolc kg-1; CEC by10.49 cmolc kg-1; exchangeable K by 0.03 cmolc kg-1; exchangeable Ca by 0.44 cmolc kg-1 and exchangeable Mg by 1.34 cmol ckg-1, compared to control.